Sensory-to-motor integration during auditory repetition: a combined fMRI and lesion study - Parker Jones, ‘Ōiwi; Prejawa, Susan; Hope, Tom; Oberhuber, Marion; Seghier, Mohamed L.; Leff, Alex P.; Green, David W.; Price, Cathy J. (Frontiers in Human Neuroscience, 2014)
The aim of this paper was to investigate the neurological underpinnings of auditory-to-motor translation during auditory repetition of unfamiliar pseudowords. We tested two different hypotheses. First we used functional magnetic resonance imaging in 25 healthy subjects to determine whether a functionally defined area in the left temporo-parietal junction, referred to as Spt (Sylvian-parietal-temporal region), reflected the demands on auditory-to-motor integration during the repetition of pseudowords relative to a semantically mediated nonverbal sound-naming task. The experiment also allowed us to test alternative accounts of Spt function, namely that Spt is involved in subvocal articulation or auditory processing that can be driven either bottom-up or top-down. The results did not provide convincing evidence that activation increased in either Spt or any other cortical area when non-semantic auditory inputs were being translated into motor outputs. Instead, the results were most consistent with Spt responding to bottom up or top down auditory processing, independent of the demands on auditory-to-motor integration. Second, we investigated the lesion sites in 8 patients who had selective difficulties repeating heard words but with preserved word comprehension, picture naming and verbal fluency (i.e. conduction aphasia). All 8 patients had white-matter tract damage in the vicinity of the arcuate fasciculus and only one of the 8 patients had additional damage to the Spt region, defined functionally in our fMRI data. Our results are therefore most consistent with the neurological tradition that emphasizes the importance of the arcuate fasciculus in the non-semantic integration of auditory and motor speech processing.